Expressions, speech acts and discourse a pedagogic interactional grammar of English - Edmondson, Willis J. 1940-2009; House, Juliane 1942-; Kádár, Dániel Z. 1979- (Cambridge University Press, 2023)
Providing a pedagogic interactional grammar of English, this book is designed for teachers and learners of English as a foreign language and textbook writers, as well as scholars of pragmatics and applied linguistics. It offers a rigorous system for capturing language use in English in a highly accessible manner